Óleos essenciais no controle de Rhizopus stolonifer e Botrytis cinerea em morangos - Passaglia, Vanessa (2017)
The strawberry (Fragaria x ananassa Duch) is very perishable and vulnerable to fungal infection, resulting in decay and economic losses. The lack of approved products to control Botrytis cinerea and Rhizopus stolonifer in postharvest strawberry results in large losses for the producer, leading to incorrect use of pesticides. For this reason, the substitution of synthetic pesticides by alternative methods is sought, such as the use of essential oils, to inhibit the growth of the fungus, and consequently the deterioration of the fruits. In view of the above, the objectives of this work were: (i) analysis of the chemical composition of the essential oils of Litsea cubeba, Foeniculum vulgare var. dulce, Pelargonium graveolens and Eucaliptus citriodora; (ii) to evaluate the in vitro effect of the volatiles of these oils on the mycelial growth of B. cinerea and R. stolonifer; (iii) to evaluate the effect of the volatiles of these oils on the germination of the conidia of B. cinerea and R. stolonifer; (iv) to evaluate in vivo the effect of volatiles of essential oils on the control of B. cinerea and R. stolonifer on strawberry fruits; (v) to evaluate in vivo the effect of the volatile of the major compound, of the most promising essential oil, in the control of B. cinerea and R. stolonifer on strawberry fruits. As for chemical analysis, the major components of L. cubeba oils, F. vulgare var. dulce, P. graveolens and E. citriodora were geranial 32.03%, trans-anethole 48.81%, citronellol 24.94% and citronellal 54.74%, respectively. In vitro the oils that were most efficient were L. cubeba and F. vulgare var. dulce, both mycelial growth and germination of conidia of B. cinerea and R. stolonifer. In vivo the essential oil of L. cubeba promoted a partial control of the diseases, already the oil of F. vulgare var. dulce and its major component trans-anethole, in the concentration of 10%, presented 100% control in strawberry fruits. Therefore, both the volatiles of the essential oil of F. vulgare var. dulce as its major component trans-anethole have potential for the control of post-harvest fungi, B. cinerea and R. stolonifer, proving to be a promising option for the development of possible phytosanitary products for the management of post-harvest diseases in strawberries.